2021
DOI: 10.2147/opth.s305968
|View full text |Cite
|
Sign up to set email alerts
|

Association of Retinal Vascular Manifestation and Obstructive Sleep Apnea (OSA): A Narrative Review

Abstract: Obstructive sleep apnea (OSA) is characterized by frequent episodes of partial or complete obstruction of the airway during sleep causing repeated episodes of apnea. OSA is more prevalent in middle-aged and older adults. OSA is associated with numerous ocular manifestations, including retinal manifestations. Literature highlighted the clear association between OSA and numerous ocular conditions including glaucoma and papilledema. This comprehensive and narrative review aims to summarize up-to-date clinical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…OSA is associated with several ocular diseases, such as nonarteritic anterior ischemic optic neuropathy, central serous chorioretinopathy, retinal vein occlusion, glaucoma, diabetic retinopathy, and AMD [ 6 , 7 , 8 , 9 , 16 ]. A possible pathological mechanism underlying AMD involves recurrent hypoxia caused by OSA, which induces angiogenesis for compensatory oxygen provision [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OSA is associated with several ocular diseases, such as nonarteritic anterior ischemic optic neuropathy, central serous chorioretinopathy, retinal vein occlusion, glaucoma, diabetic retinopathy, and AMD [ 6 , 7 , 8 , 9 , 16 ]. A possible pathological mechanism underlying AMD involves recurrent hypoxia caused by OSA, which induces angiogenesis for compensatory oxygen provision [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OSA is increasing, and it is considered a systemic disease because it is an independent risk factor for metabolic and cardiovascular disorders [ 2 , 3 , 4 ]. In addition, OSA has been implicated in several ocular diseases, including floppy eyelid syndrome, nonarteritic anterior ischemic optic neuropathy, central serous retinopathy, retinal vein occlusion, and glaucoma [ 5 , 6 , 7 ]. Accumulating evidence has indicated that patients with OSA are likely to develop age-related macular degeneration (AMD) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is linked to dry eye syndrome [17,31], keratoconus [16,17], and central serous chorioretinopathy. OSA heightens the risk of retinal vein occlusion (RVO) and diabetic retinopathy [17,32], causing damage to retinal vessels [17,32]. Venkatesh et al found increased blood flow (p = 0.011) and vessel density (p = 0.002) in the superficial capillary plexus and decreased flow (p = 0.003) and density (p < 0.001) in the deep capillary plexus among 303 high-risk OSA adult patients using the STOP-BANG questionnaire [33].…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence of neurological disorders in patients with OSA is thought to be possibly related to the frequency of apnea-induced hypoxemia ( 4 ). Besides, OSA can lead to various optic nerve impairments ( 7 , 8 ), including non-arteritic ischemic optic neuropathy (NAION) and glaucoma, as well as pathological involvement of the retinal/choroidal tissue, such as retinal vein occlusion (RVO) ( 9 , 10 ) and pachychoroidal diseases like central serous chorioretinopathy (CSC) and polypoidal choroidal vasculopathy (PCV) ( 9 , 11 ). In the last few years, a large number of scientific reviews, meta-analyses, and articles have been published to verify the significant association between OSA and glaucoma/CSC in adults ( 12 15 ), serving as the evidence of a strong association with the development of certain eye diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the pathogenesis between OSA and ocular optic nerve-related diseases or pachychoroid diseases is still unclear ( 9 ), probably associated with the abnormal hypoxia-induced factors upregulation, hypercoagulable state, oxidative stress, and endothelial cell damage secondary to hypoxia episodes ( 9 ). The related studies are mainly of clinical nature because of the long period for animal modeling.…”
Section: Introductionmentioning
confidence: 99%